Treatment of Supratentorial Anaplastic Astrocytoma’s (Subtotal Resection and Radiotherapy Vs Biopsy and Radiotherapy) - SHAFIQ, K; HAMID, N A; AHMED, M I; MIAN, J M (Annals of King Edward Medical University, 2020)
Supratentorial astrocytoma’s are the most common brain tumors. Judging the benefits of treatment for brain tumors is difficult because crude survival rates are unsatisfactory and the quality as well as the length of survival needs to be examined critically. Opinions vary as to the extent of resection ¡n these tumors. The present study proves the usefulness of subtotal excision over open minimal biopsy by comparing the post-operative quality of life enjoyed by patients undergoing these procedures. This study has shown that the patients undergoing subtotal excision enjoy a better quality of life in the late post-operative period than those who underwent open minimal biopsy.